A review on supply chain contracts in reverse logistics: Supply chain structures and channel leaderships. (15th February 2017) - Guo, Shu; Shen, Bin; Choi, Tsan-Ming; Jung, Sojin
Abstract: With the growing awareness of environmental sustainability, reverse logistics is a very timely and critical area. Traditionally, the use of supply chain contracts has been proven to be effective in enhancing the performance of logistics systems. However, the current literature on supply chain contracts in reverse logistics is scattered. As a result, we aim to review in this paper the recent state of the art literature (2006–2016) on supply chain contracts with a focus on reverse logistics systems. We explore the popularity of different kinds of supply chain contracts, and identify the most productive researchers in the area. We classify and examine the literature with respect to the supply chain structure (i.e. the involved supply chain links), and channel leaderships (i.e. who acts as the leader). Finally, we identify the research gaps, suggest five major categories of future research directions and discuss the respective research challenges.